Academic success through help-seeking behaviors among first-generation rural college students in Zhejiang province, China - Li, Ruihua (2024)
First-generation college students (FGCS) represent a unique subset within the university environment, facing distinct challenges in their educational journey, particularly in seeking academic help and achieving success. While research has explored the academic experiences of FGCS, there remains a limited understanding of their help-seeking behaviors and pathways to success. This study aims to explore how first-generation rural college students seek help to learn and achieve personal academic success, grounded in the Theory of Planned Behavior (TPB) and Academic Help- Seeking Theory. A case study approach was utilized, involving in-depth interviews with 20 first-generation rural college students at a Chinese university. Each interview lasted 60 to 90 minutes, and participants were selected through purposive sampling, focusing on those from rural backgrounds who are the first in their families to attend college. Data were analyzed using qualitative case study methods, ensuring validity and reliability through triangulation and member checking. Findings indicate that firstgeneration rural college students view academic help-seeking as crucial for success but face challenges shaped by personal and cultural attitudes. Motivations for seeking help range from aspirations for academic excellence to overcoming obstacles. Significant inhibitors include stigma and lack of resource awareness, which can deter help-seeking attempts. Initial experiences with seeking help critically impact future willingness to seek assistance. Despite difficulties, these students exhibit resilience, developing adaptive coping strategies when help-seeking does not yield the expected results. The study highlights the need for universities to provide targeted resources and support, such as academic advising, tutoring, and mentoring programs tailored to the unique needs of FGCS. Enhancing help-seeking behaviors can lead to improved academic success. Future research should explore the role of technology in facilitating these behaviors and investigate the long-term outcomes of successful help-seeking, such as academic achievement, career success, and social mobility. This study contributes to the literature by offering a comprehensive understanding of FGCS' helpseeking behaviors and practical implications for educational institutions.